Analysis of exposure indices from digital radiography exams - Isadora Veiga da Rosa; Janine Hastenteufel Dias; Rochelle Lykawka; Mauricio Anes; Luany Nobre Furlan; Alexandre Bacelar (Brazilian Journal of Radiation Sciences, 2024)
Radiography is a crucial diagnostic imaging modality in clinical practice, with persistent challenges in digital radiography regarding the level of exposure. The International Electrotechnical Commission standardized the Exposure Index (EI) and Deviation Index (DI) in digital systems, aiming to improve the assessment of radiation exposure. Each exam has an associated Target Exposure Index (EIT), representing the balance between radiation dose and image quality. This study analyzed the EI and DI of digital radiographs at a university hospital, using a database of 71,760 radiographs. The analysis considered the action limits as suggested by the American Association of Physicists in Medicine (AAPM). The group of exposures carried out in radiography rooms presented a DI of 1.2, while that of exposures carried out on mobile equipment, 2.4. In contrast, the first group presented standard deviation values between 1.5 and 3.9, while the second, between 1.8 and 2.6. These results suggest that exposures performed using Automatic Exposure Control (CAE) differ less from EIT, however, radiographic techniques were more standardized among exams with mobile equipment, performed with manual selection of exposure parameters, as these exams presented a smaller DI dispersion range. The creation of an automated tool in Google Looker Studio facilitated interactive data analysis, presenting information by anatomical region and view, with the potential to continuously monitor radiological practices. For certain incidences, the average DI values obtained differed substantially from the ideal value, which requires optimization actions, investigation into the definition of adequate EIT and calibration of the CAE. The study provided a detailed overview of local radiographic practices, highlighting priorities for optimization and standardization actions.